Experimental study on mechanical response failure mechanism of dynamic pressure roadway based on roof cutting and pressure releasing technology - YANG Zheng, DING Yanxiong, GAO Xiaojun (Meikuang Anquan, 2021)
In this paper, according to the current situation of fast deformation, large deformation amount and complicated deformation method of surrounding rock in dynamic pressure roadway, using field test and theoretical calculation method, the hydraulic roof cracking and roof cutting of working face end and gob side coal pillar roof are designed. The failure effect of cantilever beam in advance bearing pressure and arc triangle plate lateral bearing pressure in dynamic pressure roadway is analyzed, the failure mechanism of superimposed mechanical response in dynamic pressure roadway is studied, and the control countermeasures of dynamic pressure roof weak wall roadway in Xiaobaodang Mine is proposed. The results show that the pressure of the roof at the end of the working face can be effectively reduced to control the deformation of the mining roof. Adopting the cutting and pressure relief of the coal pillar roof of the adjacent goaf can effectively control the deformation of the coal pillar. The bearing capacity of the mining side and coal pillar is related to the leading and lateral supporting pressure. Combined with the actual deformation and failure status of the concrete roadway mining side and coal pillar, the dynamic pressure roadway cutting and pressure relief plan is determined. Secondary dynamic pressure strong roof weak wall roadway of Xiaobaodang Mine should adopt cutting roof pressure relief-strong roof protection technology to ensure safe mining of working face.